Project-Based Learning with Sustainability in Chemistry Learning: Developing Scientific Literacy in the 21st Century - Siti Fadilawati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Sustainability has become an increasingly important global issue in education, especially in the context of chemistry education for the 21st Century. Chemistry learning that focuses on sustainability aims to increase students' knowledge of environmental issues and equip them with the skills and values ​​needed to create a sustainable society. Scientific literacy is one of the skills that can be developed if chemistry learning applies appropriate learning models and focuses on sustainable content. This study aims to explain how project-based learning with sustainability content in chemistry learning can develop scientific literacy. The research method used a literature review. The study results show that project-based learning with sustainability in chemistry learning can encourages scientific literacy because students actively collaborate to explore sustainability issues and involve them in real-world projects that require critical, creative, and innovative thinking to solve problems and develop sustainable solutions. If these skills are developed, they can improve students' scientific literacy. Keywords: Chemistry Learning; Sustainability; Project Based Learning; Scientific Literacy.